Patient Affected by Beta-Propeller Protein-Associated Neurodegeneration: A Therapeutic Attempt with Iron Chelation Therapy - Fonderico, Mattia; Laudisi, Michele; Andreasi, Nico Golfrè; Bigoni, Stefania; Lamperti, Costanza; Panteghini, Celeste; Garavaglia, Barbara; Carecchio, Miryam; Emanuele, Elia Antonio; Forni, Gian L.; Granieri, Enrico (Frontiers in Neurology, 2017)
We here report the case of a 36 years-old patient with a diagnosis of de novo mutation of the WDR45 gene, responsible for the Beta-Propeller Protein-Associated Neurodegeneration (BPAN), a phenotypically distinct, X-linked dominant form of NBIA (Neurodegenerative Brain Iron Accumulation). The clinical history is characterized by a relatively stable intellectual disability and a hypo-bradykinetic and hypertonic syndrome with juvenile onset. Genetic investigations and T1 and T2 weighted MR images align with what is described in literature. The patient was also subjected to PET with 18- FDG investigation and Dat-Scan study. In reporting relevant clinical data, we want to emphasize the fact that the patient received a chelation therapy with Deferiprone (treatment already used in other forms of NBIA with encouraging results), which however had to be stopped because of an aggravation of the parkinsonian symptoms. Conversely, the patient has benefited from non-drug therapies and, in particular, from adapted motor activity with assisted pedaling (method in the process of validation in treatments of Parkinsonian syndromes), started before the treatment with Deferiprone and which still continues.